Calculate Road Traffic Air Emissions Including Traffic jam: Application over Ho Chi Minh City, Vietnam - Bằng, Hồ Quốc (VNU Journal of Science: Earth and Environmental Sciences; Vol 30 No 1, 2014)
Abstract: Road traffic emissions are the main sources of uncertainties in air quality numerical models used to forecast and define abatement strategies. Available models to calculate road traffic emission always require a big effort, money and time. So that in this research we used a model namely EMISENS model for calculation air emission inventories over Ho Chi Minh City (HCMC), Vietnam. However, this model can not calculated air emission inventories in temporal and take into account the traffic jam. The first aim is to improve the calculation method including phenomena of traffic jam and integrated it in the EMISENS model. Then, study scenarios to reduce air pollution caused by road traffic activities for HCMC until 2020. The results shown that when calculating emissions we have to take into account traffic jam. Emissions calculated results taking into account traffic jams shown that motorcycle emissions occupy most emissions of CH 4 , CO, NMVOC, SO 2 and NO x (more than 88%, 85%, 82%, 70 % and 31.5% respectively, of the total emissions from road transport activities in HCMC). The first scenario is the reduction scenario for the year of 2020, its results shown that the emissions of the city will be increased very low (increasing 2-8% from 2012). The current vehicle technology is old and outdated techniques. Therefore, if we want to invest in buses to replace motorcycle, air pollution in HCMC will become aggravates. Keywords: Traffic emissions; traffic jam; Ho Chi Minh City; EMISENS model; Air Pollution.